Quaternary valley levels and river terraces in the western part of the Holy Cross Mountains - Dzierżek, Jan; Lindner, Leszek; Cabalski, Krzysztof (Studia Quaternaria, 2019)
According to the current state of research five sand-gravel accumulation levels of Quaternary age are visible in the morphology of the western part of the Holy Cross Mountains, within the Wierna Rzeka, Hutka and Bobrza river valley systems and the lower stretches of the Biała Nida and Czarna Nida river valleys. Two upper levels (V and IV) correspond to valleys formed during the Odranian Glaciation-Saalian, MIS6 and its reccesional phases under the influence of proglacial and extraglacial waters beyond the extent (to the east) of the maximal ice-sheet limit of this glaciation, reaching to the present-day Leśnica-Gnieździska-Łopuszno line. Two lower levels (III and II) are terraces that were typically formed during the climatic conditions thatprevailed during Vistulian stadials. Sands and gravels of the three upper levels (V−III) contain numerous debris flow deposits and cryoturbation structures documenting periglacial conditions during their accumulation. The lowermost level (I) is a typical Holocene floodplain.
Keywords: Holy Cross Mountains; Quaternary; palaeogeography; valley sediments; fluvial forms